The lncRNAs/miR-30e/CHI3L1 Axis Is Dysregulated in Systemic Sclerosis - Valentin Dichev; Nikolay Mehterov; Maria Kazakova; Rositsa Karalilova; Anastas Batalov; Victoria Sarafian (Biomedicines, 2022)
Systemic sclerosis (SSc) is an autoimmune disease with completely undefined etiology and treatment difficulties. The expression of both protein coding and non-coding RNAs is dysregulated during disease development. We aimed to examine a possible regulatory axis implemented in the control of chitinase-3 like protein 1 (CHI3L1) or YKL-40, an inflammation-associated glycoprotein, shown to be elevated in SSc. A panel of seven miRNAs and three lncRNAs potentially involved in the control of CHI3L1 were selected on the basis of in silico analysis. TagMan assay was used to evaluate the expression levels of miRNAs and RT-qPCR for lncRNAs in white blood cells (WBCs) and plasma from SSc patients and healthy controls. Among the eight screened miRNAs, miR-30e-5p (p = 0.04) and miR-30a-5p (p = 0.01) were significantly downregulated in WBCs and plasma of SSc patients, respectively. On the contrary, the expression of the metastasis associated lung adenocarcinoma transcript 1 (MALAT1) (p = 0.044) and the Nuclear enriched abundant transcript 1 (NEAT1) (p = 0.008) in WBCs was upregulated compared to the controls. Increased levels of MALAT1 and NEAT1 could be associated with the downregulation of miR-30e-5p and miR-30a-5p expression in WBCs and plasma. We present novel data on the involvement of a possible regulatory axis lncRNAs/miR-30e/CHI3L1 in SSc and hypothesize that MALAT1 and NEAT1 could act as miR-30e-5p and miR-30a-5p decoys. This may be a reason for the increased serum levels of CHI3L1 in SSc patients.